2016
DOI: 10.1039/c5sc02921j
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of dinitroxide biradicals for efficient cross-effect dynamic nuclear polarization

Abstract: A series of 37 dinitroxide biradicals have been prepared and their performance studied as polarizing agents in cross-effect DNP NMR experiments at 9.4 T and 100 K in 1,1,2,2-tetrachloroethane (TCE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
203
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 153 publications
(220 citation statements)
references
References 71 publications
14
203
3
Order By: Relevance
“…The two-orders-of-magnitude enhancements are achieved in practice using a number of crucial elements: a paramagnetic polarizing agent in the form of a stable radical, a high-power and high-frequency microwave source (Bajaj et al, 2007; Barnes et al, 2008; Becerra et al, 1993; Gerfen et al, 1995; Rosay et al, 2010), and low temperature to slow down electron and nuclear spin relaxation. A wide variety of mono- and bi-radicals have been designed and synthesized (Kubicki et al, 2016; Michaelis et al, 2014), with the two most commonly used ones being TOTAPOL and AMUPol, which contain two nitroxide radicals separated by ~13 Å via intervening functional groups with varying lengths, rigidity and polarity (Hu et al, 2008; Hu et al, 2004; Sauvee et al, 2013; Song et al, 2006). At low temperatures of 90–120 K commonly used for DNP SSNMR experiments, a cryoprotecting solution is often used to distribute the exogenous radical uniformly in the sample and to prevent ice formation at low temperature in hydrated biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…The two-orders-of-magnitude enhancements are achieved in practice using a number of crucial elements: a paramagnetic polarizing agent in the form of a stable radical, a high-power and high-frequency microwave source (Bajaj et al, 2007; Barnes et al, 2008; Becerra et al, 1993; Gerfen et al, 1995; Rosay et al, 2010), and low temperature to slow down electron and nuclear spin relaxation. A wide variety of mono- and bi-radicals have been designed and synthesized (Kubicki et al, 2016; Michaelis et al, 2014), with the two most commonly used ones being TOTAPOL and AMUPol, which contain two nitroxide radicals separated by ~13 Å via intervening functional groups with varying lengths, rigidity and polarity (Hu et al, 2008; Hu et al, 2004; Sauvee et al, 2013; Song et al, 2006). At low temperatures of 90–120 K commonly used for DNP SSNMR experiments, a cryoprotecting solution is often used to distribute the exogenous radical uniformly in the sample and to prevent ice formation at low temperature in hydrated biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…From allylbenzyl ether, D1 was built by repetitive hydrosilylation with (dichloro)phenylsilane catalyzed by Karstedt's catalyst 48 followed by reaction with allylmagnesium bromide. Trideuteriomethyl-magnesium iodide (CD 3 MgI) was used to install the end groups to prevent fast electron and nuclear relaxations promoted by the rotations of methyl groups (–CH 3 ) at 100 K. 25,49,50 The benzyl group was then removed by homogeneous oxidative cleavage to generate the OH anchor group (Scheme 2b). We note that the typical Pd/C catalyzed reductive cleavage failed, suggesting the inaccessibility of the benzyl ether on the dendrimer to the Pd/C surface.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Zagdoun et al 22 showed that binitroxide radicals could be engineered to have longer T 1e , based on bulky, rigid skeletons, 23 and that this led to unprecedented DNP enhancements. Michaelis et al , 24 Kubicki et al 25 and Sauvée et al 26 have recently reported comprehensive studies, in which many binitroxide radicals were investigated in order to rationalize the effect of biradical structures on DNP performances. Note that hydrophobic radicals have been solubilized successfully in aqueous solutions by incorporating them into cyclic oligosaccharides or micelles.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid important CO2 adsorption in the MOF as observed in the study of Yang et al, 27 side channels that are not experimentally accessible were blocked using rare gas atoms. The Monte-Carlo simulations were done in the Grand Canonical ensemble 28 at 300 K with CO2 fugacity of 1,3,5,10,13,15,20,23,25,30,33,35,40,43, and 45 bar. For each simulation at a given CO2 fugacity, an equilibration run of one million steps took place, followed by five million steps production run.…”
Section: Si-2: In-mil-68-nh2 Forcefield Parameterizationmentioning
confidence: 99%
“…[25][26][27][28][29] Another powerful route relies on post-synthetic modification strategies. 14,[30][31][32][33] In 2011, Canivet et al reported the application of solid-phase peptide-coupling to the aminofunctionalized In-MIL-68-NH2 in order to covalently immobilize proline and alanine amino acids within the framework. 34 The successful covalent grafting of larger oligopeptides (up to tetrapeptides) was further reported for a variety of MOFs selected for their non-breathing frameworks and high pore volumes (Zr-UiO-66-NH2, In-MIL-68-NH2 and Al-MIL-101-NH2).…”
Section: Introductionmentioning
confidence: 99%